Metabolic syndrome and the risk for recurrent pre‐eclampsia: a retrospective cohort study. Issue 8 (6th March 2013) - Stekkinger, E; Scholten, RR; van der, MJ; van, APJ; Janssen, MCH; Spaanderman, MEA
<x xml:space="preserve">Abstract</x> Objective To compare the prevalence of recurrent pre‐eclampsia between women who have and do not have metabolic syndrome when non‐pregnant. Design Retrospective cohort study. Setting Three tertiary referral hospitals in the Netherlands. Population Formerly pre‐eclamptic women. Methods The presence or absence of metabolic syndrome was assessed in 480 women at least 6 months after their first pre‐eclamptic pregnancy using World Health Organization criteria. We compared the prevalence of recurrent pre‐eclampsia in the subsequent pregnancy, calculating odds ratios (OR), adjusted for confounders. Main outcome measure Recurrence of pre‐eclampsia in the subsequent pregnancy. Results Subsequent pregnancy outcome data were available for 197 women. Forty women had metabolic syndrome after previous pregnancy (20%). The prevalence of recurrent pre‐eclampsia was 18/40 (45%) in women with metabolic syndrome versus 27/157 (17%) in women without metabolic syndrome; OR 3.94 (95% confidence interval [CI] 1.86–8.33, adjusted OR 3.77 (95% CI 1.61–8.81). The risk of recurrent pre‐eclampsia increased with each extra component of the metabolic syndrome from 11.8% for absent components up to 43.9% for three or more (P for trend < 0.001). Conclusions Interpregnancy metabolic syndrome predisposes to recurrent pre‐eclampsia.